Plasmonic nanograting design for inverted polymer solar cells - Kim, Inho; Jeong, Doo Seok; Lee, Taek Seong; Lee, Wook Seong; Lee, Kyeong-Seok (OPTICAL SOC AMER, 2012)
Plasmonic nanostructures for effective light trapping in a variety of photovoltaics have been actively studied. Metallic nanograting structures are one of promising architectures. In this study, we investigated numerically absorption enhancement mechanisms in inverted polymer photovoltaics with one dimensional Ag nanograting in backcontact. An optical spacer layer of TiO2, which also may act as an electron transport layer, was introduced between nanograting pillars. Using a finite-difference-time domain method and performing a modal analysis, we explored correlations between absorption enhancements and dimensional parameters of nanograting such as period as well as height and width. The optimal design of nanograting for effective light trapping especially near optical band gap of an active layer was discussed, and 23% of absorption enhancement in a random polarization was demonstrated numerically with the optimally designed nanograting. In addition, the beneficial role of the optical spacer in plasmonic light trapping was also discussed. (C) 2012 Optical Society of America
Keywords: SHORT-CIRCUIT CURRENT; OPTICAL-ABSORPTION; CURRENT-DENSITY; ACTIVE LAYER; ENHANCEMENT; DEVICES; ORIGIN